2021
DOI: 10.1002/wsbm.1539
|View full text |Cite
|
Sign up to set email alerts
|

The tumor immune microenvironments of HPV+ and HPV head and neck cancers

Abstract: Human papillomaviruses (HPVs) are the etiological agent of a significant, and increasing, fraction of head and neck squamous cell carcinomas (HNSCC)-a heterogenous group of malignancies in the head and neck region. HPV infection accounts for approximately 25% of all cases, with the remainder typically caused by smoking and excessive alcohol consumption. These distinct etiologies lead to profound clinical and immunological differences between HPVpositive (HPV + ) and HPV-negative (HPV À ) HNSCC, likely related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 212 publications
(304 reference statements)
0
12
0
Order By: Relevance
“…In contrast, the immune-inflamed phenotype, referred to as "hot tumors", exhibited a significantly stronger response to ICIs [ 8 , 10 ]. Studies demonstrated that tumors associated viral infection often exhibit an “hot tumor” [ 11 , 12 ]. However, the impact of viral infection in tumors on the efficacy of ICIs remains a topic of debate in clinical practice, with no established consensus.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the immune-inflamed phenotype, referred to as "hot tumors", exhibited a significantly stronger response to ICIs [ 8 , 10 ]. Studies demonstrated that tumors associated viral infection often exhibit an “hot tumor” [ 11 , 12 ]. However, the impact of viral infection in tumors on the efficacy of ICIs remains a topic of debate in clinical practice, with no established consensus.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Specifically, persistent HPV infection in the host epithelium is one of the critical steps of cervical cancer development. 4,5 Current prophylactic HPV vaccines have enabled the prevention of initial infection and HPV-associated malignancies. However, HPV vaccination rates vary by state in the United States (from 31% to 79% of adolescents being HPV UTD [up-to-date]), certain high-risk HPV types are not covered in vaccines, and these vaccines will not eliminate viruses from infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Human Papillomavirus (HPV) infection causes the most common sexually transmitted diseases and up to 5% of human cancer, including anogenital cancer, and head and neck cancer 1–3 . Specifically, persistent HPV infection in the host epithelium is one of the critical steps of cervical cancer development 4,5 . Current prophylactic HPV vaccines have enabled the prevention of initial infection and HPV‐associated malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses 2023, 15, 2411 2 of 18 HNCs are a heterogeneous group of malignancies in the head and neck region that includes the oral cavity, oropharynx, hypopharynx, and larynx [6,10,11]. It is the 7th most diagnosed cancer worldwide, with approximately 890,000 new cases and 453,000 deaths in 2018 [5].…”
Section: Introductionmentioning
confidence: 99%
“…HR HPVs are responsible for approximately 25% of all HNCs, with 83% of the HPV-positive (HPV + ) subtype being caused by HR HPV16 [10,12]. In comparison to the HPV-negative (HPV − ) subtype-caused by excessive drinking and smoking-HPV + HNCs are a distinct epidemiological, molecular, and clinical entity with patients exhibiting strikingly better responses to treatment and clinical outcomes [10,11,[13][14][15][16][17]. Interestingly, HNCs caused by other HR HPVs other than HPV16 have been associated with different patient outcomes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%